Real-Time Hemodynamic Monitoring with Wearable Biosensors: Transforming Cardiovascular Management in Critical Care - Ubaid, Furqan Saddam Khudair; Khwayt, Zainab Ahmad Kadhem; Awda, Mohammed Ahmed Anim; Hussein, Sajid abdulwahed mankhi; Lakin, Zain Al-Abideen Maytham Jalil (American Journal of Botany and Bioengineering, 2025)
Hemodynamic monitoring is an essential medical practice that enables healthcare providers to effectively assess a patient’s cardiovascular health. This process grants critical insights into the progress of various diseases and the resulting treatment requirements that may arise. The application of this sophisticated monitoring technique to patients situated in critical care environments is especially imperative, as precise and accurate monitoring proves vital in facilitating the timely execution of life-saving interventions. Numerous commercial monitoring systems have been developed for this specific purpose, all designed to capture essential data in real time — a significant development that carries consequential impact on the efficacy of subsequent clinical decision-making processes. In fact, NASA recognizes hemodynamic monitoring as the greatest diagnostic advance of the twentieth century, which underlines the enormous significance of this system when it is applied to the comprehensive evaluation of an individual’s overall health status. The insights gained from these monitoring systems not only inform immediate care but also lay the groundwork for long-term health strategies that can greatly improve patient outcomes.